Divergence and Convergence on Police Transparency: Comparing Officers’ and Citizens’ Preferences on Body-Worn Camera Footage Release - Poirier, Brigitte (Canadian journal of criminology and criminal justice, 2023)
The adoption of body-worn cameras (BWCs) by law enforcement agencies is commonly viewed as a means of enhancing police transparency, holding officers accountable, and building trust with the communities they serve. The effectiveness of BWCs in promoting police transparency, however, is still debatable, with many jurisdictions still lacking clear BWC footage disclosure policies. Following a mixed-method design, this article investigates the perspectives of officers and citizens on police transparency and, more specifically, the divergences and convergences in their expectations regarding BWC footage release. The data were collected from 78 police officers (through interviews and focus groups) and 1,609 citizens from the province of Quebec (through phone surveys). The two groups share the belief that the public release of BWC footage is significant in promoting police transparency. Yet they hold differing views on its use to reach accurate assessments of police interventions. While citizens expressed worries about the integrity of BWC footage, officers appeared more concerned about the potential misunderstanding of events following the release of BWC footage. The variations in expectations between officers and the public highlight the multifaceted nature of police transparency, which should serve to inform future BWC footage disclosure policies.